TANGGUNG JAWAB NOTARIS TERHADAP AKTA YANG DIBUATNYA YANG MEMILIKI NILAI PEMBUKTIAN DIBAWAH TANGAN SESUAI PASAL 41 UNDANG-UNDANG NOMOR 2 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS - Nugraheni, KARTIKA HESTI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This study aims to assess the responsibility of the notary deed magnitude authentic proof down as a deed under hand and to assess the application of sanctions that can be given to the notary, if the deed is declared down as he made a deed under hand by the District Court. This type of research is library research it examines materials or secondary data. The data of this study are secondary data. Analysis of the data in this study is qualitative. Based on the results of research and discussion that has been done can be concluded that the first responsibility for the presence of a notary deed magnitude authentic proof down as deed under hand, if the certificate becomes null and void and cause harm to the parties, the notary can be held accountable both civil and criminal. In civil law, can be requested replace losses, costs and interest as a result of the issuance of the deed civil. In criminal decided by the court, upon a deed made by or in the presence of a Notary is concerned, it is against the deed made done a cancellation. Second, the application of sanctions that can be given to the notary, if the deed is declared down as a deed made under the hand by the District Court, if the notary proven legally and convincingly criminal transgression, then the certificate can be canceled and the notary can be sentenced to imprisonment, and can given administrative sanctions in his qualifications as a public official. Based on the administrative sanctions provided for in Article 7, Article 16, item 11 and 13, Article 17, Article 19, Article 32, Article 37, Article 54, and Article 65 A Act Number 2 of 2014 Amendment of Act Number 30 of 2004 concerning the Notary, type of administrative sanctions, namely: a written warning